Socio-demographic factors and structural barrier in accessing public clinics among the urban poor in Malaysia - Siti Norasikin Abd Wahab,; NurulHuda Mohd Satar,; Makmor Tumin, (Penerbit Universiti Kebangsaan Malaysia, 2020)
One of the dimensions of multidimensional poverty as well as quality of life is access to healthcare services. Lower income households are often associated with poorer health conditions, making accessibility to healthcare even more important. Nonetheless, in accessing healthcare services, this group of households often faces more significant personal, financial and structural barriers compared to families from higher income groups. This study focuses on structural barrier from socio-demographic factors that affects access to public clinics among the urban poor. The respondents of this study were residents of Projek Perumahan Rakyat (PPR) in Kuala Lumpur. Questionnaires were distributed to 585 respondents selected systematically from 30 PPRs. The results from the regression estimates that urban poor who are married, divorced, the spouse has passed away with monthly income less than RM 1000 are facing higher structural barrier in accessing the public clinics. Government is suggested to increase the operation hour of the public clinics as well as making effort to set up mobile kiosk clinic for urban poor live far and cannot reach the public clinics in their areas.